Advantage of Sorafenib Combined with Radiofrequency Ablation for Treatment of Hepatocellular Carcinoma. Issue 3 (May 2017) - Tang, Zhe; Kang, Muxing; Zhang, Bo; Chen, Jianke; Fang, Heqing; Ye, Qin; Jiang, Biao; Wu, Yulian
Background: Hepatocellular carcinoma (HCC) is a leading cause of death worldwide. Among the surgical and nonsurgical treatments available, radiofrequency ablation (RFA) and sorafenib have been shown to have efficacy. There is little evidence whether combination of these therapies would have additional benefits. Methods: In a mouse model of HCC, effects of sorafenib were determined by tumor size, RFA-induced necrosis area (triphenyltetrazolium chloride staining), microvascular density (MVD; 4', 6-diamidino-2-phenylindole and anti-CD31 antibody staining), and tumor perfusion (magnetic resonance imaging). Results: The RFA-induced necrosis area was 80.98 ± 9.14 and 69.49 ± 7.46 mm 2 in mice administered 80 and 40 mg/kg sorafenib, respectively, but only 57.29 ± 3.39 mm 2 in controls. Sorafenib also reduced tumor volume and enhanced RFA-induced tumor destruction in a dose-dependent manner, and reduced both MVD and tumor perfusion. Conclusions: The results of our study suggest a potential role for combining RFA with sorafenib for treatment of HCC. Sorafenib could enhance RFA efficiency, possibly through its angiogenesis suppressive effects.